Race against time: How Australians spend their time - Duncan, A; Cassells, R; Gong, H (My University, 2011)
Balancing work and family remains a big issue for Australian men and women, with around 40% of women and 30% of men feeling often or always rushed or pressed for time, according to the latest AMP.NATSEM Income and Wealth Report. But when it comes to how men and women spend their day, the report finds that there are some big differences, with traditional gender roles still evident. Contributing to time pressures, Australian full-time weekly work hours have increased by almost three hours for men and two hours for women since 1985. That is, average weekly full-time hours have risen from 39.5 to 42.3 hours for men and 36.4 hours to 38.6 hours for women. Australian women are spending on average two hours more each day than men on housework, child care and purchasing goods and services. Men spend almost the equivalent extra time on employment-related activities as well as an extra half hour per day on recreational and leisure pursuits. These are some of the key findings of the 30th AMP.NATSEM Income and Wealth Report: Race against time - How Australians spend their time, which examines time use in Australia, including time spent on employment and education; housework and childcare; leisure; and sleeping and eating; and how this has evolved
AMP NATSEM Income and Wealth Report
AMP.NATSEM Income and Wealth Report
Keywords: Employment -- Hours; Activities -- Leisure and lifestyle; Childhood and child development; Labour market; Activities; Employment; Hours; Leisure and lifestyle; Childhood and child development; Employment and unemployment